Material Function of Mycelium-Based Bio-Composite: A Review - Yang, Libin; Park, Daekwon; Qin, Zhao (Frontiers in Materials, 2021)
Mycelium-based bio-composites materials have been invented and widely applied to different areas including the construction industry, manufacturing industry, agriculture, and biomedical. As the vegetative part of a fungus, mycelium has the unique capability to utilize agricultural crop waste (e.g., sugarcane bagasse, rice husks, cotton stalks, straw and stover) as substrates for the growth of its network, which integrates the wastes from pieces to continuous composites without energy input nor generating extra waste. Their low-cost and environmentally friendly features attract interest in its research and commercialization. For example, mycelium-based foam and sandwich composites have been actively developed for construction structures. It can be used as synthetic planar materials (e.g., plastic films and sheets), larger low-density objects (e.g., synthetic foams and plastics), and semi-structural materials (e.g., paneling, flooring, furniture, decking). It is shown that the material function of these composites can be further tuned by controlling the species of fungus, the growing conditions, and the post-growth processing method to meet a specific mechanical requirement in applications (e.g., structural support, acoustic and thermal insulation). Moreover, mycelium can be used to produce chitin and chitosan, which have been applied to clinical trials for wound healing, showing the potential for biomedical applications. Given the strong potential and multiple advantages of such a material, we are interested in studying them in-depth and review the current progress of their related study in this review paper.